Monocyte Count and Systemic Immune-Inflammation Index Score as Predictors of Delayed Cerebral Ischemia after Aneurysmal Subarachnoid Hemorrhage - 이연후 (The Graduate School, Ajou University, 2024)
Objectives  _x000D_ Delayed cerebral ischemia (DCI) is a major cause of disability in patients who survive aneurysmal  subarachnoid  hemorrhage  (aSAH).  Systemic  inflammatory markers,  such  as  peripheral  leukocyte  count and systemic inflammatory index score, have been considered predictors of DCI in previous  studies. This study aims to investigate which systemic biomarkers are significant predictors of DCI. _x000D_ _x000D_ Methods _x000D_ We conducted a retrospective, observational, signle-center study of 170 patients with SAH admitted  We analyzed   3 4 and 5 7 days after admission. The DCI and non-DCI group were compared.  Variables  showing  statistical  significance  in    (P  <  0.05)  were  entered into a multivariable regression model.  _x000D_ _x000D_ Results  _x000D_ hydrocephalus, intraventricular hemorrhage, and infection showed statistical significance (P < 0.05)  on  a  univariable  logistic  regression.  Lymphocyte  and  monocyte  count systemic  inflammatory index scores and C-reactive protein levels on days 3 4, and leukocyte  neutrophil  counts  on  days  5 7  exhibited  statistical  significance  on  the  univariable  logistic  regression.  Multivariable  logistic  regression  analysis  revealed  that  monocyte  count  at  admission  (odds  ratio  [OR] = 1.64; 95% confidence interval [CI], 1.04 2.65; P = 0.036) and systemic inflammatory index  score at days 3 4 (OR = 1.55; 95% CI, 1.02 2.47; P = 0.049) were independent predictors of DCI.  _x000D_ _x000D_ Conclusions  _x000D_ Monocyte  count  at  admission  and  systemic  inflammatory  index  score  3 4  days  after  rupture  are  independent predictors of clinical deterioration caused by DCI after aSAH. Peripheral monocytosis  may be the primer for  at  days 3 4 can promptly represent the propagated systemic immune reaction toward DCI.  Keywords: Monocyte count, Systemic immune-inflammation index score, Delayed cerebral  ischemia, Aneurysmal subarachnoid hemorrhage
학위논문(석사)--의학과,2024. 8
Keywords: Aneurysmal subarachnoid hemorrhage; Delayed cerebral ischemia; Monocytes; Systemic immune-inflammation index score